Adaptation of an evidence-based intervention targeting HIV-infected prisoners transitioning to the community: the process and outcome of formative research for the Positive Living Using Safety (PLUS) intervention. - Copenhaver, Michael; Chowdhury, Sutopa; Altice, Frederick L (AIDS patient care and STDs, 2009)
No evidence-based interventions (EBIs) have been designed for implementation during the critical period when HIV-infected prisoners are being transitioned from prison to the community. We therefore conducted formative research aimed at systematically selecting and adapting an EBI that integrates HIV risk reduction and adherence to antiretroviral therapy to implement among HIV-infected prisoners transitioning back to the community. Our formative research involved a critical examination of established EBIs and associated published reports complemented by data elicited through structured interviews with key stakeholders in community and correctional settings and members of the target population. Between September 2006 and February 2007, structured one-on-one interviews were conducted with key stakeholders in the target organizations (n = 19) and with members of the target population (n = 26) in Hartford and New Haven, Connecticut. Based on the formative research, we abbreviated and adapted the Holistic Health Recovery Program targeting people living with HIV (HHRP+), an EBI, to consist of four 45-minute sessions that cover a range of prespecified topics so that participants may individually apply intervention content as needed to their own HIV risk profile and antiretroviral adherence issues. The EBI was adapted so that it could be provided in an individual or group format and delivered in either consecutive or weekly sessions and so that it could be provided within the prison system and delivered just prior to release, or in a community-based setting where it could be delivered immediately after release. This study provides a comprehensive exemplar of the process of selecting and adapting an EBI taking into account both empirical evidence and input from target organization stakeholders and target population members in real-world settings where high-risk populations are concentrated.
Keywords: Adolescent; Adult; Anti-HIV Agents; Community Networks; Evidence-Based Practice; Female; Health Promotion; HIV Infections; Humans; Intervention Studies; Interviews as Topic; Male; Outcome and Process Assessment (Health Care); Patient Compliance; Prisoners; Prisons; Risk Reduction Behavior; Young Adult